Asymptomatic Cerebral Vasoconstriction after Carotid Artery Stenting - Kang, C.H.; Roh, J.; Yeom, J.A.; Ahn, S.H.; Park, M.G.; Park, K.P.; Baik, S.K. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Carotid artery stent placement is widely performed for treatment of carotid stenosis. The purpose of this study is to present our observations on cerebral vasoconstriction in ipsilateral anterior circulation during immediate poststenting angiography in patients with near-total occlusion of the proximal ICA.MATERIALS AND METHODS: We retrospectively reviewed patient data from December 2008 to December 2018. There were 28 patients with carotid near-total occlusion. Two neuroradiologists reviewed the final cerebral angiographic finding of carotid artery stent placement to evaluate the presence of vasoconstriction or vasodilation.RESULTS: A total of 28 patients with near-total occlusion (mean ± standard deviation age, 69.0 ± 6.5 years; 92.9% male) were analyzed. Ten patients showed vasoconstriction in the treated territory, and 18 patients did not show vasoconstriction after carotid artery stenting. There were no statistically significant differences in comorbidity, frequency of symptomatic lesions, antiplatelet medication, mean procedure time, and initial NIHSS and baseline modified Rankin scale scores between the 2 groups. However, vasoconstriction is more likely to happen in patients with isolated territory from the contralateral anterior and posterior circulation (66.7% in the isolated territory group and 12.5% in the not-isolated territory group; P < .05). No headache or neurologic deficit was noted in all 10 patients with cerebral vasoconstriction.CONCLUSIONS: Cerebral vasoconstriction may occur after carotid artery stenting more frequently than expected. It occurs more frequently in patients with near-total occlusion and with isolation of the cerebral circulation. A large-scale study is necessary to assess the clinical implications of cerebral vasoconstriction after carotid artery stenting.CAScarotid artery stentingCPPcerebral perfusion pressureHPShyperperfusion syndromeNTOnear-total occlusion